Laws and Ordinances Governing the City of Chicago, Part I, Ch. 31, § 6, 88-89 (Murray F. Tuley, Bulletin Printing Company 1873 - (:unkn) unknown (General Publisher, 1873)
Forbade all persons from carrying firearms or throwing stones or other missiles within any public park.
--
Keywords: CARRY - CERTAIN PUBLIC PLACES